2021
DOI: 10.1021/acs.jcim.0c01452
|View full text |Cite
|
Sign up to set email alerts
|

Lean-Docking: Exploiting Ligands’ Predicted Docking Scores to Accelerate Molecular Docking

Abstract: In structure-based virtual screening (SBVS), a binding site on a protein structure is used to search for ligands with favorable nonbonded interactions. Because it is computationally difficult, docking is time-consuming and any docking user will eventually encounter a chemical library that is too big to dock. This problem might arise because there is not enough computing power or because preparing and storing so many three-dimensional (3D) ligands requires too much space. In this study, however, we show that qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 68 publications
(94 reference statements)
0
35
0
Order By: Relevance
“…Hierarchical workflows are similarly unattractive, because they compromise scoring function accuracy for the method that screens all compounds in order to achieve acceptable throughput. Others have modified the docking cascade to improve efficiency on large datasets. , Accordingly, there is a need for docking workflows that can find, with minimal loss of accuracy, the best scoring ligands in multibillion molecule libraries that exceed our capacities to screen or perhaps even build them explicitly, through combinatorial enumeration.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical workflows are similarly unattractive, because they compromise scoring function accuracy for the method that screens all compounds in order to achieve acceptable throughput. Others have modified the docking cascade to improve efficiency on large datasets. , Accordingly, there is a need for docking workflows that can find, with minimal loss of accuracy, the best scoring ligands in multibillion molecule libraries that exceed our capacities to screen or perhaps even build them explicitly, through combinatorial enumeration.…”
Section: Introductionmentioning
confidence: 99%
“…In order to speed up and automate conventional docking (without significant loss of valuable information), we recently developed Deep Docking (DD) – an AI-driven platform that can work in conjunction with any docking program and provides economical yet reliable access to billion-sized chemical libraries for SBVS. 19 Recently, similar approaches to DD that utilize AI to predict docking outcomes have emerged, including but not limited to MolPAL (molecular pool-based active learning), 20 lean-docking, 21 and AutoQSAR/DeepChem models. 22 Importantly, the high-throughput nature of DD can be utilized for docking ultra-large libraries but also enables the simultaneous use of multiple docking programs, facilitating the deployment of stringent consensus protocols, as advocated by the best practices of computer-aided drug design (CADD).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, computational approaches that use ligand docking scores as approximations of experimental data have been suggested. Recently, virtual screening [ 13 , 14 , 15 , 16 , 17 ] algorithms combining ML algorithms with docking scores have been suggested. Gentile et al [ 13 ] suggested a deep-docking approach that uses a docking score prediction model to reduce the resources required for docking computations.…”
Section: Introductionmentioning
confidence: 99%
“…Using this model, it was possible to increase screening enrichment by approximating the docking results of 13 million molecules of ZINC15 without performing actual docking calculations. Similarly, Berenger et al suggested a lean-docking approach that used a linear support vector regressor trained with docking scores of 10,000 molecules [ 14 ]. These results showed that efficient massive virtual screening is possible using a docking score prediction model without deteriorating the screening power.…”
Section: Introductionmentioning
confidence: 99%